Shaping the Future of English Language Teaching: Leveraging Adaptive Pedagogy and Technology for Revolutionary Learning - Juhana Juhana (Dinasti International Journal of Education Management And Social Science, 2025)
The changing dynamics of English language teaching (ELT) increasingly require creative methods that integrate adaptive pedagogy and technology to address varied student  needs. This qualitative study investigates how seasoned English teachers incorporate these strategies to improve student engagement, motivation, and metacognitive  abilities. Semi-structured interviews were performed with six teachers from diverse educational environments, and thematic analysis was employed to identify patterns and insights. The study found that teachers use digital tools such as language applications, online platforms, and multimedia resources while adjusting strategies to match students’ abilities and learning preferences This integration enhances student engagement and passion, particularly through gamified and interactive activities, while also promoting self-reflection and strategic learning, allowing students to assess and evaluate their own progress. Nonetheless, difficulties sustain, such as disparate access to technology among students and the continual necessity for professional development to align with advancing educational technologies. The research emphasizes the transformative capacity of integrating adaptive pedagogy with technology instruments, indicating a transition towards more individualized, student-centric English Language Teaching methodologies. The implications for teachers indicate that the careful integration of various methods can foster dynamic learning environments that enhance language proficiency and promote lifetime learning skills.